2018
DOI: 10.1007/s00330-017-5249-2
|View full text |Cite
|
Sign up to set email alerts
|

High-pitch low-voltage CT coronary artery calcium scoring with tin filtration: accuracy and radiation dose reduction

Abstract: • Coronary artery calcium scoring with tin filtration reduces radiation dose by 78%. • There is excellent correlation between high-pitch Sn100kVp and standard 120kVp acquisitions. • Excellent agreement regarding Agatston score categories and percentile-based risk categorization was achieved. • No cardiac risk reclassifications were observed using Sn100kVp coronary artery calcium scoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
4
25
0
1
Order By: Relevance
“…Technological developments like tin filtration and automated tube voltage selection allow for a substantial dose reduction. For example, a 100 kVp with tin filtration CACS protocol demonstrated similar Agatston scores as the reference protocol with 120 kVp despite using the standard reconstruction technique [18]. Larger deviations are expected for tube voltages like 70 and 80 kVp ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…Technological developments like tin filtration and automated tube voltage selection allow for a substantial dose reduction. For example, a 100 kVp with tin filtration CACS protocol demonstrated similar Agatston scores as the reference protocol with 120 kVp despite using the standard reconstruction technique [18]. Larger deviations are expected for tube voltages like 70 and 80 kVp ( Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…Non-contrast-enhanced, ECG-triggered, coronary calcium scoring computed tomography (CSCT) detects coronary artery calcifications (CAC) at low radiation doses [1] and is reliable in predicting future cardiovascular (CV) events for asymptomatic patients, independent of conventional risk models [2]. Clinical guidelines in the USA [3,4] and Europe [5] recommend CSCT in selected asymptomatic individuals, typically with an intermediate probability in a pre-test, clinical CV risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The current method for CAC scoring is the acquisition of a 120 kVp non-contrast-enhanced, prospective ECG-triggered cardiac CT [ 13 - 14 ]. Images obtained can then be used to evaluate the extent of calcification and assign a quantity-based total called the Agatston score determined by lesion area in square millimeters and the maximal CT Hounsfield unit [ 13 , 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…A prior study by Shemesh et al demonstrated that a CAC score of 4 or greater is a significant predictor of cardiovascular death (odds ratio 4.7, P < .0001) [ 12 ]. The use of CAC as a marker for the presence of coronary artery atherosclerosis has traditionally been quantified with dedicated cardiac CT using an electrocardiogram (ECG)-gated technique [ 13 - 14 ]. Emerging evidence suggests that CAC can be accurately assessed on non-ECG gated CT as well as LDCT.…”
Section: Introductionmentioning
confidence: 99%